2012
DOI: 10.1007/s11104-012-1295-3
|View full text |Cite
|
Sign up to set email alerts
|

The importance of root-produced volatiles as foraging cues for entomopathogenic nematodes

Abstract: Background Entomopathogenic nematodes (EPNs) are tiny parasitic worms that parasitize insects, in which they reproduce. Their foraging behavior has been subject to numerous studies, most of which have proposed that, at short distances, EPNs use chemicals that are emitted directly from the host as host location cues. Carbon dioxide (CO 2) in particular has been implicated as an important cue. Recent evidence shows that at longer distances several EPNs take advantage of volatiles that are specifically emitted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 61 publications
0
106
0
3
Order By: Relevance
“…Carbon dioxide (CO 2 ) in the soil indicates a biological activity and has been widely implicated in locating a host (Rasmann et al 2012). Turlings et al (2012) reported that the combination of this gas and specific volatile root compounds is more attractive than when encountered individually, acting synergistically to attract entomopathogenic nematodes.…”
Section: Palavras-chavementioning
confidence: 99%
“…Carbon dioxide (CO 2 ) in the soil indicates a biological activity and has been widely implicated in locating a host (Rasmann et al 2012). Turlings et al (2012) reported that the combination of this gas and specific volatile root compounds is more attractive than when encountered individually, acting synergistically to attract entomopathogenic nematodes.…”
Section: Palavras-chavementioning
confidence: 99%
“…However, following a CO 2 gradient is likely to bring nematodes to plant roots (Dusenbery, 1987), where potential hosts might then be found by moving along the roots randomly and/or in response to further directional signals operating over a shorter scale. CO 2 may be seen as a response-activator that alerts EPN to the presence of living organisms and may enhance responsiveness to other more specific cues (Turlings, Hiltpold, & Rasmann, 2012) that are discussed in more detail below.…”
Section: Dispersal and Host Finding In Soilmentioning
confidence: 99%
“…Use by EPN of plant-derived signals would be particularly important in finding hosts that are otherwise unattractive, such as vine weevil Otiorhynchus sulcatus Fabricius (Coleoptera: Curculionidae) larvae (Boff, Zoon, & Smits, 2001). However, the usefulness of the volatiles will vary depending on soil type and conditions; for example, being less effective in soil types with high levels of chemical activity (Turlings et al, 2012). Soil texture and moisture also affect diffusion of volatiles.…”
Section: Dispersal and Host-finding In The Root Zonementioning
confidence: 99%
“…The Marschner review by Turlings et al (2012) is especially noteworthy, first summarising the evidence for root volatiles as foraging cues for parasitic entomopathogenic nematodes and then presenting data to show that there may be a synergistic effect of root volatiles and CO 2 as attractants for the nematodes.…”
mentioning
confidence: 99%